Stock Market Integration in West African Monetary Zone: A Linear and Nonlinear Cointegration Approach - Agyapong, Daniel (Asian Economic and Financial Review, 2014)
The capital market plays a significant role in the development of an economy and hence an important determinant of regionalisation and single currency area formation. Stock and other capital markets have been found to predict and promote economic activities. The equity markets have been found to predict recession. As the Anglophone countries in West Africa prepare to introduce a second common currency in the region, it is imperative to assess their readiness by analysing the nature of their capital markets. The paper investigated if stock markets in the zone are integrated, since it is being suggested as the basis for common currency. Both linear and nonlinear cointegration methods were employed. The results from the linear cointegration indicated that the only active stock markets (Ghana Stock Exchange and Nigeria Stock Exchange) in the region are not integrated. However, the linear method showed a bleak sign of integration. A fractional integration method showed that whereas the Ghana Stock Exchange has infinite shock duration, the Nigeria Stock Exchange is long-lived. In effect, the markets are more of segmented than integrated, and hence appropriate for risk diversification. It is suggested that the countries work towards harmonising the capital markets through cross listing and adopting common capital market policies.